The Prevalence of Substance Misuse and its Effects among Omani College Students: A Cross-sectional Study - Al-Hinaai, Hazaa (Oman Med J, 2021)
OBJECTIVES: Many studies have confirmed that the use of alcohol, tobacco, and cannabis is prevalent among university students. This study aimed to assess the prevalence of substance misuse among college students in Oman, identifying the most commonly used substances, and reviewing the effect of substance misuse on the students’ performance. METHODS: This cross-sectional study was conducted in a higher learning institution in an urban setting in Oman from April 2018 to December 2018. A descriptive, self-administered online questionnaire, the Alcohol, Smoking, and Substance Involvement Screening Test, version 3.0 (Arabic version), adapted from the World Health Organization was sent to 12 000 students at the college. The sample size was calculated using online software (Raosoft), with a margin of error of 5% and a confidence level of 95%. RESULTS: A total of 375 students responded (response rate = 3.1%). The overall lifetime prevalence for any substance misuse (including tobacco and alcohol) among the participants was 41.3%, with the overall prevalence without tobacco or alcohol at 29.9%. Tobacco was the most common substance used, with a prevalence of around 23.5%, followed by alcohol at 10.7%. Male students had a significantly higher rate of substance abuse, for any substance, compared to female students (p < 0.001). There was a significant correlation between tobacco use, alcohol misuse, and misuse of other substances. Most of the adverse effects attributed to substance misuse reported by the respondents in this study were social (27.7%) and health-related (25.8%) problems. The impact of substance abuse on their performance was also high (23.8%). Furthermore, 15.4% of the respondents had financial problems, and 4.7%% were struggling with legal issues. Notably, only 49.1% of the respondents perceived that substance misuse was a serious problem. CONCLUSIONS: Although college students are expected to be more aware of the negative impacts of substance misuse, this study found a high prevalence of smoking, alcohol, and other substance misuses among the group of Omani college students. Further research in this field is essential, and the results of this study have shed light on a critical problem among Omani college students. It is hoped that the findings of this study will be used and built on in future research to recognize students at risk of substance misuse from early school life, leading to early intervention, and potentially preventing the possible negative consequences.